SOSIALISASI PEMAHAMAN DAN PENGENALAN AKUNTANSI SEKTOR PUBLIK DALAM MENINGKATKAN SEMANGAT BELAJAR SISWA/SISWI SMK PELITA GEDONG TATAAN UNTUK MENGHADAPI DUNIA KERJA - Apip Alansori; Rani Yunanda; Annisa Fidia Maharani; Juwita Enzelina; Milana Khanifah; Tika Pebrianti (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Vocational education aims to produce a ready-to-use workforce, but students at SMK Pelita Gedong Tataan still have a low understanding of public sector accounting due to the limited connection between theory and real-world practice. This problem has resulted in a decline in students' motivation to learn in facing professional challenges. The focus of this study was to increase awareness and enthusiasm for learning through an introduction to career prospects in government agencies. The research stages included an initial survey, material preparation, interactive socialization, and evaluation through questionnaires. Based on the results of the implementation on 21 students, a significant increase was found in their understanding of financial reports and state budget management compared to before the activity. The findings indicate that exposure to the applied material sparked students' enthusiasm to study accounting and provided a more focused career path in nonprofit organizations. Active interaction during the question-and-answer session strengthened students' mental readiness to enter the workforce. The main conclusion of this study confirms that early public sector accounting socialization effectively builds motivation and relevant competencies in vocational students. This effort successfully aligns academic expectations with industry and government needs, making graduates more adaptable to the dynamics of the workforce. With adequate knowledge, students now have greater self-confidence to pursue further education or pursue professional careers in the public sector, which is the most promising way to support the future of these graduates. ABSTRAK Pendidikan vokasi bertujuan mencetak tenaga kerja siap pakai, namun pemahaman siswa SMK Pelita Gedong Tataan terhadap akuntansi sektor publik masih rendah karena minimnya keterkaitan teori dengan praktik nyata. Masalah ini berdampak pada turunnya motivasi belajar siswa dalam menghadapi tantangan profesional. Fokus penelitian ini adalah meningkatkan kesadaran dan semangat belajar melalui pengenalan prospek karier di instansi pemerintah. Tahapan penelitian meliputi survei awal, persiapan materi, pelaksanaan sosialisasi interaktif, serta evaluasi melalui pengisian kuesioner. Berdasarkan hasil pelaksanaan pada 21 siswa, ditemukan peningkatan signifikan dalam pemahaman laporan keuangan dan pengelolaan anggaran negara dibandingkan sebelum kegiatan. Temuan menunjukkan bahwa paparan materi aplikatif memicu antusiasme siswa untuk mendalami akuntansi dan memberikan gambaran jalur karier yang lebih terarah di organisasi nirlaba. Interaksi aktif selama sesi tanya jawab memperkuat kesiapan mental siswa dalam memasuki dunia kerja. Simpulan utama penelitian ini menegaskan bahwa sosialisasi akuntansi sektor publik secara dini efektif membangun motivasi dan kompetensi relevan bagi siswa kejuruan. Upaya ini berhasil menyelaraskan ekspektasi akademik dengan kebutuhan industri serta pemerintahan sehingga lulusan lebih adaptif terhadap dinamika lapangan kerja. Dengan pengetahuan yang memadai, siswa kini memiliki rasa percaya diri lebih tinggi untuk menempuh pendidikan lanjutan maupun berkarier profesional di sektor publik yang paling menjanjikan dalam menunjang masa depan bagi lulusan tersebut.